Performance and Storage Integrity of Dried Blood Spots for PCB, BFR and Pesticide Measurements - Batterman, Stuart (2014)
Dried blood spots (DBS) can provide accurate and valuable estimates of exposure to environmental toxicants, and the use of information derived from archived newborn DBS information has enormous potential to open up new research on the impacts of early chemical exposure on disease. Broad application of DBS for the purpose of quantitative exposure estimation requires robust and validated methods. This study investigates the suitability of DBS analyses for population studies of exposure to three chemical groups: polychlorinated biphenyls (PCBs), brominated flame retardants (BFRs), and chlorinated pesticides. It examines background (matrix) contamination, recovery and extraction variability, sensitivity, and storage stability. DBS samples prepared using 50 μL of adult blood were analyzed by GC/MS, and method performance was confirmed by using certified materials and paired DBS-blood samples from six volunteers. Several of the target compounds and their degradation products have not been previously measured in DBS. All target compounds were detected in DBS samples collected from the volunteers. Sample DBS cards showed background contamination of several compounds. When stored at room temperature, target compounds, excluding PBDEs, were stable for up to one month. When refrigerated or frozen, stability was acceptable for all compounds up to one year, and multiyear storage appears acceptable at colder (e.g., −80 °C) temperatures. Multicompartment models may be used to estimate or correct for storage losses. Considering concentrations of contaminants for adults and children reported in the literature, and experimental values of detection limits and background contamination, DBS samples are suitable for quantifying exposures to many PCBs, BFRs and persistent pesticides.